Beclin1-mediated vascular autophagy negatively regulates angiogenesis and secondary neural damage in the thalamus following cerebral cortical infarction - Mengzhi Liu; Yuqian Chen; Xinyan Fan; Jinmin Gu; Shihui Xing (IBRO Neuroscience Reports, 2025)
Focal cerebral infarction induces angiogenesis in the thalamus, which influences cognitive recovery. However, the mechanisms of angiogenesis in the thalamus remain unclear. This study was designed to investigate the potential role of Beclin1-mediated vascular autophagy in angiogenesis occurring in the thalamus after cerebral infarction. Cerebral infarction was induced by middle cerebral artery occlusion (MCAO). Cognitive function was evaluated using the Morris Water Maze. We assessed secondary neuronal damage, angiogenesis, Beclin1 expression and vascular autophagy in blood vessels of the ipsilateral thalamus. The functional effects of Beclin1 on vascular autophagy, angiogenesis and angiogenesis-related factors were determined using lentiviral-delivered siRNA. The results revealed significant angiogenesis in the ipsilateral thalamus at 7 days after MCAO, concurrent with elevated LC3-I to LC3-II conversion and increased Beclin1 expression in the ipsilateral thalamic vessels. Knockdown of Beclin1 markedly suppressed vascular autophagic activation and potentiated thalamic angiogenesis at the above time point. This enhanced angiogenesis correlated with significant reductions of neuronal loss and astrogliosis in the ipsilateral thalamus, alongside improved cognitive function. Furthermore, Beclin1 knockdown significantly increased the levels of angiopoietin-2 (ANG-2) and vascular endothelial growth factor (VEGF) in the ipsilateral thalamus after cerebral infarction. Collectively, these findings implicate that inhibition of Beclin1-mediated vascular autophagy enhances angiogenesis and mitigates secondary thalamic neuronal damage following cerebral infarction. This neuroprotective effect likely related to the restoration of ANG-2 and VEGF levels mediated by vascular autophagy in the thalamus.